Plumbagin inhibits the proliferation of nasopharyngeal carcinoma 6-10B cells by upregulation of reactive oxygen species. Issue 9 (October 2018) - Li, Baisen; Gu, Xiuhui; Wu, Mingbo; Zhao, Ye; Yang, Jie; Feng, Li; Gou, Junjie; Chen, Linyi; Li, Ting; Li, Linpeng; Wang, Lan; Zhu, Li; et al.
Abstract : Plumbagin (PLB) is the primary component of the traditional Chinese medicine Baihua Dan, and possesses anti-infection and anticancer effects, with the ability to enhance the sensitivity of tumor cells to radiation therapy. However, the anticancer effect of PLB on nasopharyngeal carcinoma and the underlying mechanisms remain unclear. In this study, we investigated the anticancer effects of PLB on nasopharyngeal carcinoma 6-10B cells and clarified its molecular mechanisms in vitro . The results showed that PLB was effective against 6-10B cells proliferation in a dose-dependent manner by inducing G2/M phase cell cycle arrest. Furthermore, our data showed that PLB induced reactive oxygen species accumulation, which inhibited the GSK3β/STAT3 pathway and arrested the G2/M phase. Therefore, our results provided new insight into the mechanism of the antitumor effects of PLB, supporting PLB as a prospective therapeutic drug in nasopharyngeal carcinoma by modulating intracellular redox balance.